Revitalized β‐form crystal during the remelting and recrystallization processes in isotactic polypropylene/glass fiber composites. Issue 1 (10th July 2018) - Qin, Yijing; Zhang, Liying; Guo, Xiaobei; Dai, Kun; Schubert, Dirk W.; Zheng, Guoqiang; Liu, Chuntai
Abstract: Under different pre‐shear temperatures, an interfacial sheath structure is fabricated by pulling a single glass fiber in isotactic polypropylene melt. The thermal stability of sheath structure and "crystalline memory effect" of β‐form crystal are studied thermo‐optically. The thermal stability of primary sheath structure is influenced by the orientation of molecular chains and pre‐shear temperature. During tens of remelting and recrystallization processes, the number of "revitalized" β‐form crystal generally decreases. However, the nucleation density of α‐form crystal exhibits no obvious change, indicating that α‐form crystal has stronger "crystalline memory effect" than that of β‐form crystal. More interestingly, some crystal nuclei of β‐form crystal can "revitalize" continuously or fitfully during the recrystallization. The findings preliminarily indicate that "crystalline memory effect" of β‐form crystal might not only depend on the orientation level of molecular chains of sheath structure, but also depend on the spatial arrangement of fibrillar lamellae in sheath structure. Abstract : The thermal stability of sheath structure and "crystalline memory effect" of β‐form crystal are studied thermo‐optically by remelting and recrystallization. The former is influenced by the orientation of molecular chains and pre‐shear temperature, while the latter not only depends on the orientation level of molecular chains of sheath structure, but also depends on the spatial arrangement of fibrillar lamellae in sheath structure.